The oppressive boss and workers' authoritarianism: effect of voice suppression by supervisors on employees' authoritarian political attitudes. Issue 5 (19th October 2020) - Stanojevic, Antonia; Akkerman, Agnes; Manevska, Katerina
ABSTRACT: This study examines the relationship between employee voice suppression by workplace authorities (i.e. supervisors) and the formation of employees' attitudes towards political authority. We test whether the effect of experienced voice suppression by supervisors on employees' preference for authoritarian governance is positive, negative or nonlinear. The hypotheses are tested on original data gathered within the Dutch Work and Politics Survey 2017 ( N = 7599), which allows for a wide range of demographic and organisational control variables. The results favour a nonlinear effect of suppression on employees' authoritarianism. These results support the notion that political attitudes are dynamic and that the workplace plays a role in shaping them.